The Productivity Paradox: Does Happiness Matter? - Farooq Rasheed1; Eatzaz Ahmad (NUST Journal of Social Sciences and Humanities, 2021)
Productivity paradox refers to a situation when investment in information technology is inversely related with economic growth. We test the hypothesis whether economic happiness plays a moderating role between information related capitalization and economic growth and thus may or may not invalidate the productivity paradox. Using 20 years annual panel data of OECD and APT economic blocs, happiness moderates the relationship between inputs labour and capital productivities with output growth in both the economic blocs. Economic Happiness is thus recommended to be boosted in getting effective labour and capital productivities.